Detection of rabies virus – specific antibodies in Wild mammals from a rainforest area, São Paulo, Brazil using RFFIT, SFIMt and ELISA techniques - Araújo, D. B.; Wasniweski, M.; Rodrigues, C. S.F.; Campos, A. C.A.; Martorelli, L. F.A.; Kataoka, A.P. de A.G.; Cunha, E. M.S.; Durigon, E. L.; Favoretto, S. R. (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
The emergent importance of rabies in wild animals in Brazil demonstrates the necessity of continuous epidemiological surveillance in these animal species aiming the development of better strategies for the prevention and control of the disease. The use of blood serum samples from several wild species captured in a native Rainforest area in the North coast of São Paulo State, Brazil, was an excellent opportunity for the research of rabies virus circulation among wildlife in the region, and also to compare different techniques for antibodies detection. In this study we used the “Rapid Fluorescent Focus Inhibition Test – RFFIT, the Simplified Fluorescent Inhibition Microtest – SFIMT and the Enzime Linked Immunosorbent Assay – ELISA techniques for the detection of rabies virus-specific antibodies in terrestrial wild mammals. Out of 139 samples, 15 (10,8%) presented positive titers for RFFIT (“gold standard” for detection of rabies virus neutralizing antibodies), 50 (35,9%) positive titers for SFIMT and 02 (1,43%) positive titers for ELISA. When comparing RFFIT and SFIMT, 100 (72%) samples presented concordant results when considering positive and negative titers. These results are an evidence of rabies virus circulation between the wild animal species (mainly opossums, capuchin-monkey and coati) in the studied area, even when considering the low concordance between RFFIT and SFIMT. The discordant results between ELISA and RFFIT or ELISA and SFIMT, (99,3%), can be due to the fact that the ELISA kit used was developed for vaccinated foxes, and when considering the Brazilian fauna, which present a great species variety without the use of oral vaccination, the efficacy of the technique could be affected. This result indicates the importance of continuous research regarding a better knowledge of the role presented by wild animals in rabies circulation and transmission in Brazil. Epidemiologic studies in different regions of the Country could provide a valuable information regarding the prevention and control of the disease, and also aiming the standardization and validation of the different diagnostic serologic techniques, especially considering the great and unique variety of animals present in our Country. Acknowledgments: Gaia Consultoria Ambiental, Fundação de Amparo a Pesquisa do Estado de São Paulo (FAPESP) and Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES).